Cyclosporine plus avatrombopag versus cyclosporine monotherapy for first-line treatment of elderly patients with transfusion-dependent non-severe aplastic anemia: a single center retrospective study - Zhuxin Zhang; Qinglin Hu; Leyu Wang; Chen Yang; Miao Chen; Bing Han (Annals of Medicine)
Background Elderly patients with transfusion-dependent non-severe aplastic anemia (TD-NSAA) face limited treatment options owing to transplantation incompatibility and safety concerns.Methods Data from older patients (≥60 years) newly diagnosed with TD-NSAA and had been treated with either avatrombopag (AVA) + cyclosporine (CsA) or CsA monotherapy at our center were retrospectively collected.Results In total, 52 patients were enrolled, with 26 receiving AVA + CsA and 26 receiving CsA monotherapy. The overall response (OR) rate was higher in the AVA + CsA group than in the CsA group at the 1st, 2nd, 3rd, 6th months, and at the end of the follow-up (all p < 0.05). The complete response (CR) rate was higher in the AVA + CsA group than in the CsA group at the 6th month and at the end of follow-up (p = 0.017 and 0.039). Patients receiving AVA + CsA had a shorter time to achieve the first response (p = 0.008) and CR (p = 0.010) than those receiving CsA monotherapy. Furthermore, patients receiving AVA + CsA exhibited a higher rate of platelet transfusion independence at the 3rd (p = 0.041), 6th (p = 0.008) months, and likewise at the end of the follow-up (p = 0.097).Conclusions The addition of AVA to CsA can significantly improve the OR or CR rate and platelet levels with acceptable side effects in elderly patients, which implies that the combination is a viable alternative for elderly patients with TD-NSAA.